Layered self-assemblies for controlled drug delivery: A translational overview. (June 2020) - Sarode, Apoorva; Annapragada, Akshaya; Guo, Junling; Mitragotri, Samir
Abstract: Self-assembly is a prominent phenomenon observed in nature. Inspired by this thermodynamically favorable approach, several natural and synthetic materials have been investigated to develop functional systems for various biomedical applications, including drug delivery. Furthermore, layered self-assembled systems provide added advantages of tunability and multifunctionality which are crucial for controlled and targeted drug release. Layer-by-layer (LbL) deposition has emerged as one of the most popular, well-established techniques for tailoring such layered self-assemblies. This review aims to provide a brief overview of drug delivery applications using LbL deposition, along with a discussion of associated scalability challenges, technological innovations to overcome them, and prospects for commercial translation of this versatile technique. Additionally, alternative self-assembly techniques such as metal-phenolic networks (MPNs) and Liesegang rings are also reviewed in the context of their recent utilization for controlled drug delivery. Blending the sophistication of these self-assembly phenomena with material science and technological advances can provide a powerful tool to develop smart drug carriers in a scalable manner.